PERAN DUKUNGAN TEMAN DAN LINGKUNGAN RANTAU DALAM MENINGKATKAN MOTIVASI BELAJAR MAHASISWA - Dinda Aulia aceh; Siti Annisa Anis; Tiara Hennisa Tiara (Yayasan Baitul Hikmah al-Zain, 2026)
This study aims to determine the influence of peer support and the overseas living environment on the learning motivation of students at UIN Syahada Padangsidempuan. The background of this research is the challenges faced by overseas students in adapting both academically and socially, which requires external support to maintain learning motivation. The research employed a quantitative method with data collected through questionnaires. The sample consisted of 120 overseas students selected using purposive sampling. The data were analyzed using multiple linear regression. The results revealed that peer support has a positive and significant effect on learning motivation, and the overseas living environment also significantly affects students’ learning motivation. Simultaneously, both variables contribute significantly to improving the learning motivation of students at UIN Syahada Padangsidempuan. This research highlights the importance of social relationships and a supportive environment for overseas students in achieving academic success.